Pembingkaian Pilihan Raya Legislatif Aceh 2014: satu analisis kandungan terhadap berita dalam talian akhbar Kompas dan Republika - Novarini , Susanti; Omar, Bahiyah (Universiti Malaya, 2016)
This study examines the coverage of the 2014 legislative election in Aceh by two Indonesian national newspapers; Kompas and Republika. The objectives are to identify the dominant frame used by the two newspapers and the changes in the use of frames during the campaign and after the polling. Online news articles were selected using purposive sampling for a period of 128 days starting from 11 January to 18 May, 2014, with a total of 193 articles analyzed. This study used quantitative content analysis to achieve the objectives of the study. The results show a significant difference in the use of news frames (i.e: conflict, horse race, regional perspective and constitutional crisis frames) between Kompas and Republika. There was no significant difference in the use of human interest and issue/policy frames. It was found that issue/policy frame was the most dominant frame used by both newspapers. The study also found a significant change in the use of news frames for the two periods; during and after the election. The use of all frames was significantly higher during the election as compared to after the election except for horse race. This frame appeared more frequently after the election as the highlights of the election shifted to issues concerning victories and accomplishments of the contesting political parties and candidates.